Profil Kromatografi Lapis Tipis Produk Fraksinasi Dingin Campuran Cpo (Crude Palm Oil) dan Pko (Palm Kernel Oil) - Muhammad Ferdiansyah Mulya Harahap (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
Oil palm fruit processing industry produce crude palm oil (CPO) and palm kernel oil (PKO). Products derived oil palm fruit as an emulsifier and antimicrobial is a monoglycerides (MG) and diglycerides (DG). The research previously, reported that cold fractionation products mix PKO-CPO known to have antibacterial properties and good emulsifier. In this study aims to determine the value of the yield, the pattern of separation and antimicrobial activity of compounds separate components. Identification technique have used the Thin Layer Chromatography (TLC) silica gel. The research methods have used single factor with three repetitions. The single factor is used mixture of hexane, diethyl ether, and formic acid = 80: 20: 2 (v / v) 30 ml in the chamber. The observed distribution patterns based on the Rf value, the value of yield and antimicrobial activity test by the method agar diffusion on Eschercia coli, Staphylococcus aureus, and Saccaromhyces cerevisiae. The results purification of cold fractionation product mix CPO and PKO have produced five separate component fractions determined based on the value of Rf is monogliserydes (MG),dilgiserydes (DG), free faty acid (FFA), and trigliserydes (TG). The yield fractions separate components MG, DG, ethyl ester (EE), ALB, and TG residue have produced respectively by 24.75%, 24.89%, 12.45%, 24.63%, and 13.27%. The total yield combined of MG and DG have averaged of 49.65%. The highest composition MG-DG cold fractionation products (52.54%) with the remainder TG (12.48%).